2010
DOI: 10.1136/ard.2009.119495
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, vascular injury and repair in rheumatoid arthritis

Abstract: The systemic pro-inflammatory state present in patients with rheumatoid arthritis (RA) accelerates the progression of atherosclerosis through chronic endothelial activation. Uncoupling of endothelial nitric oxide synthase plays a central role in the amplification of oxidative signalling pathways that chronically activate and, ultimately, injure the endothelium. Recent studies indicate that the resultant loss of endothelial integrity in patients with RA may also involve defects in the vascular regenerative pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…Several studies report that there is higher cardiovascular morbidity and mortality in the patients affected by autoimmune arthritis compared to the general population [17][18][19][20][21][22][23][24]. The articular inflammation causes an overexpression of mediators such as articular and systemic proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies report that there is higher cardiovascular morbidity and mortality in the patients affected by autoimmune arthritis compared to the general population [17][18][19][20][21][22][23][24]. The articular inflammation causes an overexpression of mediators such as articular and systemic proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a is a strong proinflammatory cytokine that causes neutrophilic chemotaxis, macrophage activation, and increased superoxide production. All of these may cause endothelial disorder and atherogenesis [17][18][19][20][21][22][23][24]. Endothelium normally reduces these processes through the NO benefits, therefore, the endothelial dysfunction is recognized as an atherosclerosis precursor [25,26] and as a ''barometer'' of the cardiovascular functionality [27].…”
Section: Discussionmentioning
confidence: 99%
“…15 The most important factors in the pathogenesis of cardiovascular disease in patients with RA are endothelial dysfunction and vessel wall damage. 16 It has been speculated that cardiovascular complications seen in patients with JIA start with vascular damage years before symptoms present. 17 Accordingly, a recent study revealed that subclinical cardiovascular changes tended to present earlier, particularly in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In rheumatoid arthritis, this risk approaches the risk of patients with diabetes 36. The pathogenesis of this increased risk is largely enigmatic, but is proposed to arise from a chronic inflammatory environment, causing vascular damage and plaque formation 37 38. The occurrence of atherosclerotic plaques has been related to an increasing chronological age 11.…”
Section: Discussionmentioning
confidence: 99%